Impact of Depressive Symptoms on Antiepileptic Drug Adherence Among Epilepsy Patients - Wali Ahmed, Faisal; Tasawar, Areej; Maroof, Sobia; Tasawar, Ayesha; Mirza, Warda; Butt, Mehwish; Ayaz Khan, Junaid; Bano, Sher; Shehzad, Rida (International Journal of Basic and Applied Sciences, 2025)
Background: Epilepsy patients frequently develop depression among psychiatric illnesses because ‎these conditions diminish both their ability to stick to their medication regimen and their life ‎satisfaction. ‎Methods: Researchers conducted a cross-sectional study that involved 300 adult epilepsy patients. ‎They utilized three assessment instruments, including the Patient Health Questionnaire-9 (PHQ-9), Morisky Medication Adherence Scale (MMAS-8), and Quality of Life in Epilepsy Inventory (QOLIE-31). Multiple regression and correlation are data analysis methods. Data was collected ‎from September 2024 to March 2025.‎Results: In this sample of 300 participants, 188 males comprised 63% of the total, while women ‎made up the remaining 37%, with 112 participants. Most patients presented with moderate to ‎severe depressive symptoms, which strongly affected their medication adherence levels while also ‎producing negative impacts on their quality of life. A total of 69 people (23%) claimed they did not ‎experience seizures during the past 6 months, whereas 111 participants (37%) stated they had ‎encountered one seizure, and another 95 (32%) responded they had multiple monthly seizures. The ‎analysis through regression revealed depressive symptoms as the strongest predictor for ‎substandard use of AED medications (β = .754, p < .01). ‎Conclusion: The presence of depressive symptoms acts as a key obstacle for proper AED use ‎while producing substantial negative effects on epilepsy patients' quality of life. Professional ‎psychological testing and combined mental health treatments should be conducted regularly to help ‎achieve better outcomes in clinical care‎.
Keywords: Epilepsy; Depression; Antiepileptic Drugs; Medication Adherence; Quality of Life